Dietary spirulina supplementation modifies rumen development, fermentation and bacteria composition in Hu sheep when consuming high-fat dietary - Wang, Zhibo; Liang, Yaxu; Lu, Jiawei; Wei, Zongyou; Bao, Yongjin; Yao, Xiaolei; Fan, Yixuan; Wang, Feng; Wang, Daxiang; Zhang, Yanli (Frontiers in Veterinary Science, 2023)
Spirulina is rich in carotenoids and fatty acids. The objective of this study was to investigate the long-term effects of spirulina supplementation in a high-fat diet (HFD) on rumen morphology, rumen fermentation and the composition of rumen microbiota in lambs. The 44 lambs were fed with either a normal chow diet (NCD), a high fat diet based on basal diet (HFD, no Spirulina supplement,), or the high fat diet supplemented with 3% spirulina (HFD+S), The results showed that spirulina supplementation improved the concentration of volatile fatty acids and rumen papilla length. Meanwhile, there was an increased tendency in rumen weight and the expression of rumen tight junction genes Claudin-1, Claudin-4, and Occludin were also upregulated in HFD+S group. Spirulina supplementation also significantly changed the rumen microbiota composition in HFD group by 16S rRNA high-throughput pyrosequencing. Moreover, the richness and diversity of rumen microbiota were significantly down-regulated with spirulina supplementation, such as the relative abun-dance of Prevotella 9 and Megasphaera significantly increased in HFD group compared to NCD group, while spirulina supplementation could reverse the change of bacteria composition. Overall, 3% spirulina supplementation 60 days can be used in Hu sheep diets to improve rumen microbe caused by HFD diet.